PENERAPAN MODEL HAZARD UNTUK MEMPREDIKSI KEBANGKRUTAN: STUDI PADA PERUSAHAAN YANG DELISTING DI BURSA EFEK INDONESIA - Aulia Keiko Hubbansyah; I Gusti Ketut Agung Ulupui; Ari Purwanti (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. The aim of this study is trying to identify a group of variables that can beused to predict firm bankruptcy. The examined variables consist of Net Income to TotalAssets (NIMTA), Total Liabilities to Market Value of Total Assets (TLMTA), Cash toMarket Value of Total Assets (CASHMTA), Relative Size (RSIZE), Excess Return(EXRET), Volatility of Return (SIGMA), Stock Price (PRICE) and Market to BookEquity (MB). By using Hazard Model as a modelling basis, the result of this studyfound there were six variables that could be used as a predictor of firm bankruptcy,including TLMTA, TLMTAsq2, TLMTAsq3, EXRET, SIGMA dan PRICE. Theevaluation of the model showed that it has a good accuracy. In accordance with modelaccuracy approaches, the level of accuracy of the model showed a range between89.36-96.51 percent; Area Under Curves (AUC) of ROC Curves reached 0.8476; andthe Brier Score showed a very low number which was 0.0309.Keywords: Model Hazard, Bankruptcy Firm.